2016
DOI: 10.5120/ijca2016910497
|View full text |Cite
|
Sign up to set email alerts
|

Sequence to Sequence Weather Forecasting with Long Short-Term Memory Recurrent Neural Networks

Abstract: The aim of this paper is to present a deep neural network architecture and use it in time series weather prediction. It uses multi stacked LSTMs to map sequences of weather values of the same length. The final goal is to produce two types of models per city (for 9 cities in Morocco) to forecast 24 and 72 hours worth of weather data (for Temperature, Humidity and Wind Speed). Approximately 15 years (2000-2015) of hourly meteorological data was used to train the model. The results show that LSTM based neural net… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
33
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 125 publications
(34 citation statements)
references
References 5 publications
0
33
0
1
Order By: Relevance
“…In the same year, a model was developed to predict the temperate in Nevada using a deep neural network with stacked denoising auto-encoders with higher accuracy of 97.97% compared to traditional neural networks (94.92%) [35]. In 2016, the multi-stacked deep learning LSTM approach was utilised to forecasting weather parameters temperature, humidity, and wind speed [36]. The author suggested that the model could be used to predict other weather parameters based on the effectiveness and accuracy of the results.…”
Section: Related Workmentioning
confidence: 99%
See 1 more Smart Citation
“…In the same year, a model was developed to predict the temperate in Nevada using a deep neural network with stacked denoising auto-encoders with higher accuracy of 97.97% compared to traditional neural networks (94.92%) [35]. In 2016, the multi-stacked deep learning LSTM approach was utilised to forecasting weather parameters temperature, humidity, and wind speed [36]. The author suggested that the model could be used to predict other weather parameters based on the effectiveness and accuracy of the results.…”
Section: Related Workmentioning
confidence: 99%
“…The proposed model is a Single-input single-output and able to produce a state-of-the-art performance for up to 6 h Forecasting the weather of Nevada: a deep learning approach [35] This model accepts four input parameters and predicts one output as temperature. Results indicated that stacked denoising auto-encoder deep learning model predicts accurate long-term temperature Sequence to sequence weather forecasting with long short-term memory recurrent neural networks [36] Multi-stacked LSTMs are used to map sequences of weather values of the same length. Use three input parameters and predict one parameter at a time A deep learning methodology based on bidirectional gated recurrent unit for wind power prediction [62] Contributed the bidirectional gated recurrent network for wind power forecasting.…”
Section: Weather Research and Forecasting (Wrf) Modelmentioning
confidence: 99%
“…Best results were obtained from the model consisting of 3 hidden layers constituting 300, 500 and 200 neurons. In [18], 15 years of hourly meteorological data for 9 cities in Morocco was analyzed by authors using multi-stacked LSTM to forecast 24 and 72 hours weather data. Missing values were eliminated using forward filling and RMSProp optimizer was used.…”
Section: Literature Reviewmentioning
confidence: 99%
“…It is advantageous to train and model meteorological data with time series characteristics and to conduct forecast research using the LSTM. Akram and El [29] used 15 years of hourly weather data to train the multilayer LSTM model and to forecast meteorological conditions out to 24 and 72 hours. ey found that the LSTM can forecast general weather variables with a better accuracy.…”
mentioning
confidence: 99%